2021
DOI: 10.1177/23259671211014206
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence in the Management of Anterior Cruciate Ligament Injuries

Abstract: Background: Technological innovation is a key component of orthopaedic surgery. With the integration of powerful technologies in surgery and clinical practice, artificial intelligence (AI) may become an important tool for orthopaedic surgeons in the future. Through adaptive learning and problem solving that serve to constantly increase accuracy, machine learning algorithms show great promise in orthopaedics. Purpose: To investigate the current and potential uses of AI in the management of anterior cruciate lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Accuracy of up to 98% has been reported, as well as the potential of CNNs to outperform or perform non-inferiorly to humans. 26 , 32 - 36 It has also been reported that DL models could recognize laterality, exam view, and body part in wrist, hand, and ankle radiographs. They have also shown promise in achieving more notoriously difficult diagnoses, such as scaphoid fractures, as effectively as human specialists.…”
Section: Image Recognition and Diagnosticsmentioning
confidence: 99%
See 3 more Smart Citations
“…Accuracy of up to 98% has been reported, as well as the potential of CNNs to outperform or perform non-inferiorly to humans. 26 , 32 - 36 It has also been reported that DL models could recognize laterality, exam view, and body part in wrist, hand, and ankle radiographs. They have also shown promise in achieving more notoriously difficult diagnoses, such as scaphoid fractures, as effectively as human specialists.…”
Section: Image Recognition and Diagnosticsmentioning
confidence: 99%
“…The past decade has seen imaging analysis become a considerable focal point among AI research. 32 Numerous authors have studied the ability of CNNs to identify various upper and lower limb fractures on radiographs, such as hip, calcaneus, and radial fractures. Accuracy of up to 98% has been reported, as well as the potential of CNNs to outperform or perform non-inferiorly to humans.…”
Section: Image Recognition and Diagnosticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Timeline outlining the major historical steps that have led to the development of artificial intelligence (AI) up to the advancement of deep learning, with significant impact in the history of medicine and orthopedics. AI, ML, and DL offer a variety of application models in the orthopedic field, including the random forest model, support vector machine, multilayer perceptron, convolutional neural network (CNN), alternating decision trees, and recurrent neural network [4,15].…”
Section: Ai Toolsmentioning
confidence: 99%